1990
DOI: 10.1902/jop.1990.61.12.755
|View full text |Cite
|
Sign up to set email alerts
|

A Family Study of a Mother and Daughter with Increased Susceptibility to Early‐Onset Periodontitis: Microbiological, Immunological, Host Defensive, and Genetic Analyses

Abstract: Microbiological, immunological, host‐defensive, and genetic analyses were performed on a mother and daughter, both of whom had early‐onset periodontitis (rapidly progressive periodontitis in the mother; localized juvenile periodontitis in the daughter). Microscopic examination revealed a greatly elevated percentage of rod‐form bacteria in both subjects. Fusobacterium sp. and Porphyromonas gingivalis (formerly Bacteroides gingivalis) were the predominant microorganisms cultured. The humoral immune responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 26 publications
0
60
0
Order By: Relevance
“…However, studies reported to date have not shown much consistency in the association of HIL.A phenotype with periodontal disease. Nishimura et al (1990) reported that the association between HLA antigens and periodontal disease differs from race to race. Suzuki et al (1985) reported that depressed neutrophil functions is not restored after periodontal therapy and suggested that such neutrophil dysfunction is congenital.…”
Section: General Blood Examinationmentioning
confidence: 99%
“…However, studies reported to date have not shown much consistency in the association of HIL.A phenotype with periodontal disease. Nishimura et al (1990) reported that the association between HLA antigens and periodontal disease differs from race to race. Suzuki et al (1985) reported that depressed neutrophil functions is not restored after periodontal therapy and suggested that such neutrophil dysfunction is congenital.…”
Section: General Blood Examinationmentioning
confidence: 99%
“…However, several forms have been reported in the same family.10,25,27,29"31 Some authors have postulated that localized and generalized JP are clinical variants of the same condition,31 and that the generalized form is a later and more severe expression of the localized disease.32 However, in some families the generalized form has been noted in younger individuals, while older siblings display only the localized form.29 Since these disorders frequently occur in the same family, it has been suggested that they have related genetic causes. 25,31 Another approach to the study of genetic risk factors in periodontal disease is to examine associations between disease and inherited tissue markers. Some conditions such as ankylosing Spondylitis and coeliac disease are strongly associated with certain HLA specificities, which suggest that genes which confer susceptibility to these disorders are in linkage disequilibrium with genes in the major histocompatibility complex (HLA specificities are encoded by class I and II MHC genes).…”
Section: Juvenile Periodontitismentioning
confidence: 99%
“…Yet today, the precise reasons for such familial clustering remain largely unclear, although the genetic mechanism for commonly occurring chronic diseases is generally acknowledged to have a complex etiology (Potter, 1990;Nishimura et al, 1990). In its traditional and most restrictive form, the family method for ascertainment of information about the heritability of certain characteristics consists of pedigree analysis.…”
Section: Family Studiesmentioning
confidence: 99%